Risk analysis techniques of oil and gas pipeline (Revista de Investigaciones Universidad del Quindío, 2022)
The safety of pipelines that transport energy has become an important and controversial issue with the general public. The main hazard for safe transportation of substances is a pipeline failure taken as a loss of its tightness and release of the transported medium to the environment. To perform reliability analysis and estimation of accident risk level, Fault Tree Analysis (FTA) and Event Tree Analysis (ETA) are two graphical techniques used to perform a risk analysis, where FTA represents causes and their probabilities of failures, and ETA represents consequences of a failure event. Failure of oil transmission pipelines was analyzed by fault tree analysis in this project, and the probability of internal corrosion, one of the root causes, has been evaluated by applying the physical reliability model. According to failure modes of pipeline, leakage and rupture, a fault tree of the pipeline was constructed. Minimal cut sets of the fault tree have been shown, and the failure probability of a top event and the important analyses of basic events were evaluated by quantitative analysis. In conventional fault tree analysis, probabilities of the basic events were treated as precise values. At last, the probability of different accident scenarios that may result from failed oil pipeline due to pipe rupture has been estimated.
Keywords: Reliability analysis; Risk analysis; Fault tree; Event tree; Physical reliability model; Corrosion; Oil pipeline rupture